Comparison of Robot-Assisted Surgery Versus Laparoscopic Surgery in Colorectal Surgery: A Systematic Review of Operative and Postoperative Outcomes - Gede Bayu Wedanta Netra; Putu Yudis Pramana Karang (The International Journal of Medical Science and Health Research, 2026)
Background: Along with the increasing trend of robotic surgery adoption, various healthcare centers are beginning to consider transitioning from open or laparoscopic approaches to robot-assisted surgical techniques for the management of rectal cancer. Methods: A literature search was conducted on the Medline (via PubMed), Google Scholar, and ResearchGate databases to find relevant articles from early 2014 to January. All randomized clinical trials (RCTs) and prospective studies comparing robotic surgery with open or laparoscopic rectal resection were included. Results: A total of 15 RCTs and 11 prospective studies with a total of 6,922 patients were included. The review results showed that robotic surgery was associated with less blood loss, lower surgical site infection rates, shorter hospital stays, and higher rates of negative resection margins compared to open surgery. Compared to laparoscopy, robotic surgery showed lower conversion rates, less blood loss, lower reoperation rates, and lower mortality. However, operative time and procedure costs for robotic surgery were higher compared to both approaches. Conclusion: The robotic approach is a safe and effective option for rectal resection, with clear advantages over open surgery. For centers transitioning from laparoscopic techniques, cost considerations need to be carefully calculated.